A turn for the bad [large type] - Connolly, Sheila (Connolly, Sheila. County Cork mysteries., 2016)
Boston expat Maura Donovan still has a lot to learn about Irish ways -- she didn't only inherit a pub, she inherited a tight-knit community. When a local farmer out for a stroll on the beach with his son mysteriously disappears, Maura decides to investigate. But this time she may be getting in over her head.